Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T16:51:10+01:00
A)
x=-y
x-y=6

x=-y
-y-y=6

x=-y
2y=6 /:(-2)

x=-y
y=-3

x=3
y=-3

b)
y=x+3
2x+y=9

y=x+3
2x+x+3=9

y=x+3
3x=9-3

y=x+3
3x=6 /:3

y=x+3
x=2

x=2
y=5

c)
x-4y=15
y=4x

x-4*4x=15
y=4x

y=4x
x-16x=15

y=4x
-15x=15 /(-15)

x=-1
y=-4

d)
y=-2x-1
x=y+7

x=y+7
y=-2(y+7)-1

x=y+7
y=-2y-14-1

x=y+7
y+2y=-15

x=y+7
3y=-15 /:3

y=-5
x=2

e)
-3x=2y
y=1-x

y=1-x
-3x=2(1-x)


y=1-x
-3x=2-2x

y=1-x
-3x+2x=2


y=1-x
-x=2

x=-2
y=3
f)
{5x-2y=0
{7x+4y=0

-2y=-5x(-1) [ wyznaczyliśmy y]
{7x+4y=0

2y=5x
7x + 10x=0

x=0
y=0
g)
x+3y=3
x-y=1 /+y

x+3y=3
x=1-y

1-y+3y=3 /-1
x=1-y

-y+3y=2
x=1-y

2y=2 /:2
x=1-y

y=1
x=1-1

y=1
x=0
h)
3m-n=9 /-3m
2m-5n= -11

-n=9-3m /× -1
2m-5n= -11

n=-9 - (-3)m
2m-5n=-11

2m-5(-9-(-3)m)=-11
n=-9 - (-3)m

2m- (-45) - (-15)m = -11 /+(-45)
n=-9 - (-3)m

2m - (-15)m = - 11 +(-45)
n=-9 - (-3)m

17 m = -56
i)
5x=4-2y
4x=y=3

5x=4 - 2(4x)
4x=y=3

5x=4-8x /+8x
4x=y=3

13x=4 /÷13
4x=y=3

x=4/13

j)x+3y=3
x-y=5

x+3y=3
x=5+y

5+y-3y=3
x=5+y

-2y=-2
x=5+y

y=1
x=5+1

y=1
x=6
Mam nadzieje że pomogłam , liczę na naj ;-)
2 3 2